2022
DOI: 10.1155/2022/4733220
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Simulation of the Market Risk Early-Warning Model Based on Deep Learning Methods

Abstract: To address the problem of low efficiency of existing forecasting models for market risk warning, a market risk early-warning model based on improved LSTM is suggested utilizing the whale optimization algorithm (WOA) to optimize the number of hidden layer neurons and time step parameters of long short-term memory. The proposed market risk early-warning model is validated by using 40 real estate companies as the research subjects and 20 relevant variables such as gross operating income, net profit asset growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In recent years, LSTM has been mainly used in natural language processing, economics, energy power, and transportation forecasting. (2022) constructed a market risk early warning model based on the Whale Optimization Algorithm (WOA) and LSTM, which has a prediction accuracy of greater than 96% for market risk [26]. The aforementioned study showed that LSTM is a time series Recurrent neural network suitable for processing and predicting time series data, which fits well with the characteristics of financial data.…”
Section: Deep Learning Modelmentioning
confidence: 99%
“…In recent years, LSTM has been mainly used in natural language processing, economics, energy power, and transportation forecasting. (2022) constructed a market risk early warning model based on the Whale Optimization Algorithm (WOA) and LSTM, which has a prediction accuracy of greater than 96% for market risk [26]. The aforementioned study showed that LSTM is a time series Recurrent neural network suitable for processing and predicting time series data, which fits well with the characteristics of financial data.…”
Section: Deep Learning Modelmentioning
confidence: 99%